Robot Pembersih Lantai Otomatis Berbasis Arduino Uno - Darusman, Darusman; Abbas, Aries; Firmanto, Angga Dwi (INFORMATICS FOR EDUCATORS AND PROFESSIONAL : Journal of Informatics, 2025)
The Arduino-based automatic floor cleaning robot is a system designed to assist in the floor cleaning process efficiently without human intervention. This system uses an ultrasonic sensor to detect obstacles and a dust sensor to measure and display the amount of dirt particles absorbed by the vacuum cleaner. The Arduino Uno is used as the main controller, regulating the robot's movement using DC motors and processing sensor data to be displayed on an LCD as a cleanliness indicator. This study employs a hardware programming method with an experimental approach, where the robot is tested in an environment with obstacles and dust particles as the main objects. Testing is conducted to evaluate navigation effectiveness and dust suction capability. The results show that the robot can operate automatically, avoid obstacles, and clean floors with a fairly high level of efficiency. This research contributes to the development of home automation technology by introducing a more efficient and autonomous floor cleaning robot solution. With this system, it is expected to improve room cleanliness without requiring direct human involvement.